Kebijakan Utang Koperasi Mahasiswa UNY Untuk Meningkatkan Kinerja Koperasi - Tejo Nurseto (Jurnal Pendidikan Akuntansi Indonesia, 2011)
This research wants to investigate whether such variables profitability, assets andfixed asset ratio influenced debt policy in KOPMA UNY. We were choose thesevariables cause many factors can affect debt decision. We examined by using linearregression.The result shows that the three variables have positive and significant influences todebt. It was proved by t-tests and coefficients. Profitability (PROF) has coefficient of1,799 with t-test of 10,055 and significance of 0,000, ASET has coefficient of 0,579with t-test of 3,735 and significance of 0,001 and fixed asset ratio (FAR) hascoefficient of 0,185 with t-test of 4,822 and significance of 0,000. The goodness offit (R2) is 0,468 which mean that variables choosed can explaine the dependentvariable by 46,8 percents. The numbers was quiet enough to be an estimator.KOPMA UNY has opportunity to expand their business, with a good performance onthese variables. They can attain the sources of fund such as banking and others.Key words : debt, profitability, asset, fixed asset ratio